Application of Arduino for Current Sensorless Self Regulated Power Factor Correction - Y.Alexander Jeevanantham, R.Muthusundaram, Rahul kumar mohanty, G.Ranjith (Mathematical Statistician and Engineering Applications, 2022)
It is well known that the power factor (PF) will decrease as inductive loads are introduced to the market. If the PF drops, the price of electricity will increase. Our system's automated capacitor sets are activated when the PF drops, and they restore the PF to a predetermined level. Our research is distinctive in that an IoT (Internet of Things) technology was employed to carry it out. In addition to monitoring from the research work display, it will be able to monitor and control the research work from any location on the Internet. An Arduino Uno Microcontroller has been used as the programming tool. The PF can be improved to boost equipment voltage, increase current carrying capacity, reduce power losses, and lower electricity costs. PF correction capacitors are reactive current generators. By balancing the nonworking power used by inductive loads, we help to raise the PF. The PF of a load is measured in this article using an Arduino Uno microcontroller, after which the required capacitors are triggered to account for reactive power and bring the PF closer to unity.